Feasibility of deescalating postoperative care in enhanced recovery after cardiac surgery - Stock, Sina; Berger Veith, Sarah; Holst, Theresa; Erfani, Sahab; Pochert, Julia; Dumps, Christian; Girdauskas, Evaldas (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Enhanced Recovery After Surgery (ERAS) prioritizes faster functional recovery after major surgery. An important aspect of postoperative ERAS is decreasing morbidity and immobility, which can result from prolonged critical care. Using current clinical data, our aim was to analyze whether a six-hour monitoring period after Minimally Invasive Cardiac Surgery (MICS) might be sufficient to recognize major postoperative complications in a future Fast Track pathway. Additionally, we sought to investigate whether it could be possible to deescalate the setting of postoperative monitoring. Methods: 358 patients received MICS and were deemed suitable for an ERAS protocol between 01/2021 and 03/2023 at our institution. Of these, 297 patients could be successfully extubated on-table, were transferred to IMC or ICU in stable condition and therefore served as study cohort. Outcomes of interest were incidence and timing of Major Adverse Cardiac Events (MACE; death, myocardial infarction requiring revascularization, stroke), bleeding requiring reexploration and Fast Track associated complications (reintubation and readmission to ICU). Results: Patients' median age was 63 years (IQR 55-70) and 65% were male. 189 (64%) patients received anterolateral mini-thoracotomy, primarily for mitral and/or tricuspid valve surgery (n=177). 108 (36%) patients had partial upper sternotomy, primarily for aortic valve repair/ replacement (n=79) and aortic surgery (n=17). 90% of patients were normotensive without need for vasopressors within 6h postoperatively, 82% of patients were transferred to the general ward on postoperative day 1 (POD). Two (0.7%) MACE events occurred, as well as 4 (1.3%) postoperative bleeding events requiring reexploration. Of these complications, only one event occurred before transfer to the ward - all others took place on or after POD 1. There was one instance of reintubation and two of readmission to ICU. Conclusions: If MICS patients can be successfully extubated on-table and are hemodynamically stable, major postoperative complications were rare in our single-center experience and primarily occurred after transfer to the ward. Therefore, in well selected MICS patients with uncomplicated intraoperative course, monitoring for six hours, possibly outside of an ICU, followed by transfer to the ward appears to be a feasible theoretical concept without negative impact on patient safety.